Improving Student Listening Ability Through Audio-Visual Application At Smpn 2 Painan - Yefridelti Yefridelti (Jurnal Ilmiah Pendidikan Scholastic, 2018)
To learn a lesson well, we need to hear, see, ask questions about it, and discuss it with others. Not only that, teachers need to "do it", that is to describe something in their own way, to show their example, to try to practice their skills and to do tasks that demand the knowledge they have gained.Problems that want to be studied in this research are: Is using Audio-Visual model in students of class IX SMP Negeri 2 Painan year 2015 – 2016. Steps in using the Audio-Visual implementation method? This research was conducted in class VII of SMP Negeri 1 Painan. This place was chosen because based on the results of class observations and interviews with English teachers in the classroom it can be concluded that the skills of students listening in English is still low. This is because teachers do not use adequate techniques, limited books that are in school and media equipment is still lacking. Research time. This research was conducted from early October as a description of the implementation of this study can be seen in the following table: This stage is intended to thoroughly review the actions that have been done, based on data that has accumulated in the previous step. And look for difficulties experienced by students and teachers in the process of action that has been done. Students are invited to discuss each cycle to ask about their difficulties. The teacher reflects on past events as the process of action takes place. All the data obtained are analyzed and evaluated to refine the action in the next cycle or whether or not the treatment given to the students is continued. By knowing that the triggers of low learning activity and learning achievement are in factors such as the method used by the teacher, so the use or replacement of conventional methods into constructivist methods is indispensable, consequently the researchers tried the Audio-Visual learning model in an attempt to solve problems at school. Based on the low learning activities and student achievement that are presented on the background of the problem, the use of Audio-Visual learning model attempted to be able to complete the purpose of this research is to know the improvement of student achievement. How much improvement has been made clear at the end of the analysis. From the results of the research presented in Chapter IV and all the data that have been submitted, the research objectives submitted can already be achieved. To answer the purpose of research is the achievement of student prestai achievement can be seen evidence that has been submitted. From the baseline data almost all students got the score below, then in cycle I decreased to 8 students and cycle II scores all students above the standard specified in the school. From the initial average of 4.5 increased to 6.3 in cycle I and on the second cycle rose to 7.9. From the initial data no students are complete while in cycle I become more that 4 students and on cycle II all students reach mastery.From all supporting data proving the achievement of learning objectives can be submitted that Audio-Visual model can give the expected answers according to the purpose of this study. All this can be achieved is due to the readiness and hard work of researchers from the time of making the proposal, review the things that have not been good with friends of teachers, preparation of grids and research instruments, the use of means of data triangulation to the implementation of the maximum research.